Ambient electrospray deposition Raman spectroscopy (AESD RS) using soft landed preformed silver nanoparticles for rapid and sensitive analysis. Issue 24 (1st November 2019) - Ahuja, Tripti; Ghosh, Atanu; Mondal, Sandip; Basuri, Pallab; Jenifer, Shantha Kumar; Srikrishnarka, Pillalamarri; Mohanty, Jyoti Sarita; Bose, Sandeep; Pradeep, Thalappil
Abstract : Ambient electrospray deposition Raman spectroscopy (AESD RS) using soft landed preformed silver nanoparticles for rapid and sensitive SERS analysis. Abstract : We introduce a technique called ambient electrospray deposition Raman spectroscopy (AESD RS) for rapid and sensitive surface-enhanced Raman scattering (SERS) based detection of analytes using a miniature Raman spectrometer. Using electrospray, soft landing of preformed silver nanoparticles (AgNPs) was performed for 30–40 seconds for different concentrations of analytes deposited on conducting glass slides. Using AESD RS, SERS signals were collected within 4–6 minutes, including sample preparation. Transmission electron microscopy (TEM) and dark-field microscopy (DFM) were used to characterize the preformed AgNPs before and after electrospray. We achieved the nanomolar and micromolar detection of p -mercaptobenzoic acid ( p -MBA) and 2, 4-dinitrotoluene (2, 4-DNT), respectively. In this work, 0.3 μL of preformed AgNPs were used, which is ∼33 times less in volume than the quantity needed for conventional SERS. Quantitation of unknown concentration of analytes was also possible. A similar amount of electrosprayed AgNPs was utilized to characterize Escherichia coli ( E. coli ) bacteria of different concentrations. Viability of bacteria was tested using fluorescence microscopic imaging. Besides reduced analysis time and improved reproducibility of the data in every analysis, which is generally difficult in SERS, the amount of AgNPs required is an order of magnitude lower in this method. This method could also be used to probe the real-time changes in molecular and biological species under ambient conditions.